Last Judgment iconography in the Carpathians - Himka, John-Paul, 1949- (University of Toronto Press, 2009)
"Few subjects in Christianity have inspired artists as much as the Last Judgment. Last Judgment Iconography in the Carpathians examines over 100 images of the Last Judgment, with an emphasis on those from the fifteenth century to the eighteenth century, in the Carpathian mountain region of Ukraine, Poland, Slovakia, and Romania. John-Paul Himka's analysis of these monumental works of art allows him to consider history free from the traditional frameworks and narratives of nations. For nine years, Himka studied Last-Judgment images throughout the Carpathians and found a distinctive and transnational blending of Gothic, Byzantine, and Novgorodian art in the region." "Piecing together the story of how these images were produced and how they developed, Himka traces their origins on linden boards and their evolution on canvas and church walls. Originally painted by monks, these images increased in popularity and eventually came to be commissioned and even painted by peasants and shepherds whose tastes so shocked bishops that they ordered the destruction of depictions of sexual themes and grotesque forms of torture. A richly illustrated and detailed account of history through a style of art, Last Judgment Iconography in the Carpathians will find a receptive audience with art historians, religious scholars, and Slavists."--Jacket.